A method for depositing tin oxide film. - Wan Yunus, Wan Md. Zin; Ebrahimiasl, Saeideh; Kassim, Anuar; Zainal, Zulkarnain (2011)
The present invention relates to a method for depositing tin oxide film on a substrate comprises of providing a substrate; preparing a precursor solution comprises of metal dichloride, hydrogen peroxide and a complexing agent; adjusting the precursor solution at a predetermined pH; maintaining the precursor solution at a predetermined temperature; immersing; and drying the substrate. The tin oxide film is deposited on the substrate by chemical bath deposition at a room temperature.